STUDIES ON HYPHOMYCETES-I - R. S. SAWANT, M. S. PATIL and (Indian Phytopathology, 2002)
Present paper deals with eight Hyphomycetous species studied and described herein. These are Cercospora arthraxonis sp. nov., C. coicis sp. nov., Cercosporidium uitis sp. nov., Sporidesmium litseae sp. nov., Stenella ceropegiae sp. nov., Trochophora simplex (petch) R. T. Moore, Xenosporium africanum Piroxynski and Zygosporium majus Pirozynski.